Semigroups of endotopisms of efficient and connected relations - Toichkina, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
For binary relations satisfying the conditions of efficiency and connectedness, it is shown that the semigroup of all endotopisms of any effective and connected binary relation characterizes this relation to within an isotopism or an antiisotopism.